1998
DOI: 10.1007/bf02237487
|View full text |Cite
|
Sign up to set email alerts
|

Blood selenium and glutathione peroxidase status in patients with colorectal cancer

Abstract: These results support the hypothesis of an association between low selenium level and advanced tumor disease. From our data, it cannot be decided whether this phenomenon is more likely to be a consequence or a causative factor for development and course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…In this context, the human plasma/ serum Se-proteins glutathione peroxidase type 3 (GPx3) and Seprotein P (SelP), as well as the Se-containing protein Se-albumin (SeAlb, for simplicity also refereed below as a Se-protein) are of high interest. An inverse correlation has been observed between various types of cancer (including CRC) and serum GPx3 or plasma SelP [4,23,24], but other works did not confirm this data [12,25]. To our knowledge only a single study by Early et al [12] took into account the complete plasma Se-proteins status in CRC.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this context, the human plasma/ serum Se-proteins glutathione peroxidase type 3 (GPx3) and Seprotein P (SelP), as well as the Se-containing protein Se-albumin (SeAlb, for simplicity also refereed below as a Se-protein) are of high interest. An inverse correlation has been observed between various types of cancer (including CRC) and serum GPx3 or plasma SelP [4,23,24], but other works did not confirm this data [12,25]. To our knowledge only a single study by Early et al [12] took into account the complete plasma Se-proteins status in CRC.…”
Section: Introductionmentioning
confidence: 56%
“…Colorectal cancer (CRC) is the third most commonly diagnosed form of cancer in women and fourth in men worldwide [2], and its association with Se has been investigated in a number of studies. Some of them observed a significantly lower level of Se in serum of CRC patients than in healthy subjects, or a significantly higher risk to develop CRC and lower cumulated cancerrelated survival rates for subject presenting low serum Se levels [3][4][5]. A similar behaviour was noticed in patients affected by colorectal adenoma, the precursor lesion in most CRC cases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 70%
“…In the study from the Canada performed on a total of 1048 incidence cases (402 CRC) a statistically significant inverse associations between toenail selenium level and the risk of colon cancer for both genders combined (OR, 0.42; 95% CI, 0.19-0.93; p = .009) and for female subjects (p = .050) were observed [14]. The results of the retrospective study performed in Germany showed, that patients with a selenium level <70 μg/l had a significantly lower mean survival time and a lower cumulative cancer-related survival rate than patients with a selenium level >70 μg/l (p = 0.0009) [15]. The association between selenium status and risk of large size colorectal adenomas in a geographical area with a low selenium status were described also by group from the Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Selenium concentrations in the literature are not considered if only presented in the form of figures [154]. The interested reader, who would like to obtain more information about factors influencing blood selenium concentrations, is referred to a literature review [5], or to the following references for recent values in: children: [37][38][39][40][41][42][43][44][45][46]48,149,[155][156][157][158][159][160]; adolescents: [161][162][163][164] or elderly people: [49][50][51][52][53][54][55][56][57][58][165][166][167][168][169][170][171][172][173][174][175][176].…”
Section: Selenium Concentrations In Healthy Adults From Other Europeamentioning
confidence: 99%